Microstructural and mechanical properties elucidation on VAL12 aerospace alloy tailored with La2O3 dispersoids fabricated by squeeze casting technique for tribological applications. (2020) - Srinivasan, S.A.; babu, S.P. Kumaresh
Abstract: Rare earth oxide reinforced Aluminium matrix composite are produced using La2 O3 as dispersoids in VAL12 aluminium alloy matrix by varying the percentage of dispersoids. The composites are tested for their microstructural evolution and mechanical properties. Advanced characterization techniques are used in characterizing the composites to reveal the microstructural and physical properties. The microscopic examination reveals refinement in grain structure with increasing reinforcement percentage of La2 O3 . XRD results shows peak broadening of matrix and increase in the intensity of dispersoids peak confirming the presence of reinforcement in the matrix. Energy dispersive spectrum mapping further confirms the elemental composition of the composites. The actual density of the composites are more than 95% of the theoretical density as the squeeze casting process produces with very less porosity level. The tensile test results show loss of ductility in the composites having dispersoids more than 4% (by wt.) which was further elucidated with the fractographic and machining studies. Fractographic results show fracture propagating in both matrix and reinforcement as there is good interface between matrix and reinforcement. The machining studies on developed composites reveal continuous, semi continuous and disintegrated chips, revealing increase in brittle nature with respect to increase in dispersoids percentage